Continuity and coordination of care in highly selected chronic cancer patients treated with multiple repeat radiation therapy - Sebastian M. Christ; Maiwand Ahmadsei; Annina Seiler; Eugenia Vlaskou Badra; Jonas Willmann; Caroline Hertler; Matthias Guckenberger (Radiation Oncology, 2021)
Abstract Introduction and background As cancer is developing into a chronic disease due to longer survival, continuity and coordination of oncological care are becoming more important for patients. As radiation oncology departments are an integral part of cancer care and as repeat irradiation becomes more commonplace, the relevance of continuity and coordination of care in operating procedures is increasing. This study aims to perform a single-institution analysis of cancer patients in which continuity and coordination of care matters most, namely the highly selected group with multiple repeat course radiotherapy throughout their chronic disease. Materials and methods All patients who received at least five courses of radiotherapy at the Department of Radiation Oncology at the University Hospital Zurich from 2011 to 2019 and who were alive at the time of the initiation of this project were included into this study. Patient and treatment characteristics were extracted from the hospital information and treatment planning systems. All patients completed two questionnaires on continuity of care, one of which was designed in-house and one of which was taken from the literature. Results Of the 33 patients identified at baseline, 20 (60.6%) participated in this study. A median of 6 years (range 3–13) elapsed between the first and the last visit at the cancer center. The median number of involved primary oncologists at the radiation oncology department was two (range 1–5). Fifty-seven percent of radiation therapy courses were preceded by a tumor board discussion. Both questionnaires showed high levels of experienced continuity of care. No statistically significant differences in experienced continuity of care between groups with more or less than two primary oncologists was found. Discussion and conclusion Patients treated with multiple repeat radiation therapy at our department over the past decade experienced high levels of continuity of care, yet further efforts should be undertaken to coordinate care among oncological disciplines in large cancer centers through better and increased use of interdisciplinary tumor boards.